In vitro biofilm formation on different ceramic biomaterial surfaces: Coating with two bactericidal glasses. Issue 6 (June 2019) - Llama-Palacios, A.; Sánchez, M.C.; Díaz, L.A.; Cabal, B.; Suárez, M.; Moya, J.S.; Torrecillas, R.; Figuero, E.; Sanz, M.; Herrera, D.
Abstract: Objectives: To compare biofilm formation on the surface of different ceramic biomaterials to be used in implant dentistry. Methods: In vitro biofilm formation was investigated from mixtures of standard reference strains of Streptococcus oralis, Veillonella parvula, Actinomyces naeslundii, Fusobacterium nucleatum, Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis . Sterile ceramic calcium hydroxyapatite discs (HA) as control, sterile Al2 O3 /Ce-TZP nanocomposite sandblasted discs (material A1) and sterile Al2 O3 /Ce-TZP nanocomposite sandblasted discs and coated with two types of antimicrobial glasses (materials A2 and A3) were used. Biofilms were grown on the four surfaces and evaluated after 12, 24, 48 and 72 h of incubation. Biofilms were examined by confocal laser scanning microscopy (CLSM). In addition, counts of live bacterial cells of the target species A. actinomycetemcomitans, F. nucleatum and P. gingivalis were calculated by quantitative polymerase chain reaction (qPCR) combined with propidium monoazide (PMA). For data analysis, bacterial counts were compared with a multivariate general lineal model. Results: Using CLSM, cell vitality decreased in A2 and A3. With qPCR-PMA, significant differences in vitality were observed for A. actinomycetemcomitans in A3 after 48 and 72 h of incubation. With respect to the development of the biofilms, a significant increase in counts on HA and materials A1 and A2 was observed for A. actinomycetemcomitans and F. nucleatum . Conversely, for P. gingivalis, no differences were found for HA and materials A1 and A2. Significance: Differences in biofilm formation were detected among the different tested materials. The ceramic material A3 has an effect on the vitality of A. actinomycetemcomitans growing in an in vitro biofilm model.